1996
DOI: 10.3109/15563659609013832
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Phosphide Ingestion—A Clinico-pathologic Study

Abstract: Aluminum phosphide when ingested is highly toxic with fatal dose as low as 1.5 g. The dominant clinical feature is severe hypotension refractory to dopamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
4
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 10 publications
6
83
4
2
Order By: Relevance
“…[4] However, mortality rate in the present study was lower than previous reports [1,4,17]. In the study by Shadnia and colleagues, death occurred in 31% of the studied patients [1] and in the study by Singh et al mortality rate was as high as 59% [17]. Perhaps, it can be explained by relatively short interval from intoxication to hospital admission in our study.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…[4] However, mortality rate in the present study was lower than previous reports [1,4,17]. In the study by Shadnia and colleagues, death occurred in 31% of the studied patients [1] and in the study by Singh et al mortality rate was as high as 59% [17]. Perhaps, it can be explained by relatively short interval from intoxication to hospital admission in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…The lethal dose of AlP in human has not well determined, and it has been reported that it can be varied from 0.4 to 1.5 g [16,17]. Interestingly, some authors have suggested that there is no association between AlP-ingested dose and mortality [1] which may be due to accidental and/ or intentional errors in reporting number of ingested tablets by patients or their family members.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, about 80% of patients had gastrointestinal symptoms characterized by nausea and vomiting. It has been reported in similar studies that in most cases the patients poisoned with aluminium phosphide have specific gastrointestinal symptoms [10][11][12], however the overall conclusion is that despite the high prevalence of gastrointestinal symptoms, the lack of gastrointestinal symptoms does not reject the chance of aluminium phosphide poisoning. The age and the gender ratio in this article was, respectively, 27.2 ±7.26 years and 14 male vs 9 female, in a study by Soltaninejad et al [13] age and gender were similar to the current article.…”
Section: Discussionmentioning
confidence: 76%
“…W połą-czeniu ze wstrząsem mogą one prowadzić do śpiączki lub zaburzeń świadomości (delirium) [9]. Powszechnie występujące powikłania zatrucia fosforkiem glinu obejmują: krwotok, ostrą niewydolność nerek, zespół rozsianego wykrzepiania wewnątrznaczyniowego i zaburzenia rytmu serca [10]. Z uwagi na to, że zatrucie fosforkiem glinu stanowi poważny problem dla zdrowia publicznego i wiąże się z wysoką śmiertelnością celem niniejszego badania była ocena profilu laboratoryjnego pacjentów po zatruciu fosforkiem glinu leczonych w szpitalu Razi w latach 2010-2015.…”
Section: Introductionunclassified
See 1 more Smart Citation